The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11422-016-9787-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of inquiry-based science education in different countries: some reflections

Abstract: In this forum article, I reflect on issues related to the implementation of inquirybased science education (IBSE) in different countries. Regarding education within the European Union (EU), the Bologna system has in later years provided extended coordination and comparability at an organizational level. However, the possibility of the EU to influence the member countries regarding the actual teaching and learning in the classrooms is more limited. In later years, several EU-projects focusing on IBSE have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…The changes in science teaching both in Europe and the whole world are undoubtedly connected with the introduction of open inquiry methods in the education process (Rocard Report 2007, Dunne et al 2013, Rundgren 2016, Uum van Martina et al 2016, Heinz et al 2017. However, the popularisation of the IBSE strategy is not always reflected in updates of teacher training courses at universities.…”
Section: Issues From Chapters Related To the Place Of The Earth In Thmentioning
confidence: 99%
“…The changes in science teaching both in Europe and the whole world are undoubtedly connected with the introduction of open inquiry methods in the education process (Rocard Report 2007, Dunne et al 2013, Rundgren 2016, Uum van Martina et al 2016, Heinz et al 2017. However, the popularisation of the IBSE strategy is not always reflected in updates of teacher training courses at universities.…”
Section: Issues From Chapters Related To the Place Of The Earth In Thmentioning
confidence: 99%
“…Researchers (Hodgetts, et al, 2015;Ramnarain & Hlatswayo, 2018;Ramnarain & Schuster, 2014) have identified several benefits of IBSE, which include: Understanding of scientific concepts and phenomena; development of critical thinking skills, rational decision-making, problem-solving skills; enhancement of learners' acquisition of scientific practices; and motivation of learners to study science, and to pursue science related careers. In acknowledgment of the importance of IBSE, many countries have established educational projects and programs (Scientix in Belgium, Fibonacci in France, SiS Catalyst in the United Kingdom, and Primas in Germany, as listed by Rundgren [2018]) that promote the IBSE pedagogy.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, teachers need to ensure the teaching approach applied is able to capture students' interest, curiosity, and inquiry. To achieve this requires a creative and innovative approach which can lead to an effective science education (Trna et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, an inquiry-based approach is the process of finding the problems and solving the problems (Yu & Li, 2018). Students need to solve the problems, conduct self-investigations, and work in groups with the guidance from the teachers (Trna et al, 2012). This approach is a constructivist approach that is different from the didactic approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation